KAJIAN PERBEDAAN METODE APLIKASI KALSIUM KARBIDA 250 mg/L TERHADAP KECEPATAN PEMBRONDOLAN SERTA NILAI DOBI, KAROTEN DAN VITAMIN E PADA TANDAN BUAH SEGAR DI STIP-AP MEDAN - Samosir, Jojor Indriani; Giyanto, Giyanto; Aisyah, Siti; Mulyara, Budi (Jurnal Agro Fabrica, 2022)
Semi Virgin Crude Palm Oil (SVCPO) is the palm oil product that is managed from raw material TBS palm oil that given treatment using chemical material like etephone and calcium carbide. The TBS was treated by using simple tools and short processing, with minimum treatment with temperature that was already modified. The purpose of the research is to develop the managing process of CPO that maintain the quality of minor component with DOBI value that is produced by acceleration technic variation in managing the palm fruit. The research was done in Sekolah Tinggi Ilmu Pertanian Agrobisnis Perkebunan (STIP-AP). The research time was done during January until August 2016. The research uses the Rancangan Acak Lengkap (RAL) method, by giving chemical material to the raw material TBS by method treatment like spray, injection, and combination. The result of the research shows that SVCPO has carotene ranges 506-1044 Ppm, E vitamin ranges 509-771 Ppm, and DOBI ranges 2,47-3,61. Etephone and calcium carbide material give the real effect if it is looked from the method, and give the unreal effect if it is looked from the chemical material concentration. So it is concluded that inside this research method that the best to DOBI and E vitamin is injection method.